Perlindungan Hukum Anak Korban Perceraian dalam Perkawinan Campuran di Indonesia - Rosalinda, Rosalinda (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Advances in science and technology have made it easier to establish relationships between individuals, nations, and even countries. These interactions often lead to mixed marriages, both between couples of different nationalities and between workers from different countries. However, mixed marriages often present challenges, especially when it comes to registering the marriage, which can be confusing: should it be done in the husband's or wife's country of origin? Additionally, differences in nationality and cultural backgrounds frequently lead to conflicts within the household, which in some cases result in divorce. This situation directly impacts the children of mixed marriages, particularly regarding their nationality status and legal protection of their rights.